A systems modelling and simulation approach to gear shift effort analysis. (29th October 2004) - Marco, J.; Ball, R.; Jones, R.P.; Lillie, K.
Synchronized gear shift quality is a major contributor to vehicle refinement. A number of papers have recently presented analytical methods for studying shift quality. However, in these papers consideration is given to the transmission in isolation from the dynamics of the powertrain and the external environment. In order to obtain a more holistic understanding of the phenomena, the use of a systems modelling and simulation strategy is adopted. A mathematical model of a conventional transmission is formulated. The model is employed in conjunction with the shift quality measures to provide numerical information relating to how the gear shift performance of a vehicle is affected by external factors acting on the transmission and also to variations of pertinent transmission parameters. Particular consideration is given to operation of the vehicle in an off-road environment and variations in input pinion inertia.